Vibration in nuclear plant : proceedings of the 3rd International Conference on 'Vibration in nuclear plant' held on 11-14 May 1982. (ICE Publishing, 1983)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.